Diversidade, cidadania e direitos : concepção de professores/as sobre uma disciplina de núcleo comum da Universidade Estadual de Goiás nos cursos de bacharelado - Moreira, Thiago Rodrigues (2019)
This research is the result of the Postgraduate Program in Education, Language and Technologies of the State University of Goiás (PPG-IELT), whose problem was to reveal the perspectives and challenges of teachers in the discipline of diversity, citizenship and rights of the State University of Goiás (UEG), regarding the conception of experiences, portraits and teacher’s perception about the discipline in the baccalaureate courses, which is one of the common core discipline of the (new) curriculum matrix (BRAZIL, 2014). It was sought to understand how the teachers who work in the baccalaureate courses establish their knowledge to minister the discipline of Diversity, Citizenship and Rights. As a methodological course the qualitative approach was used in the perspective of an approach to the phenomenological, exploratory and bibliographic method. Having presented the general objective, it was established the specific objectives that permeated the research in identifying the objectives and institutional competences of the discipline of Diversity, Citizenship and Rights of the UEG; analyzing the core terms of the subject and teaching knowledge with the theoretical references of the authors and authors: Andrade; Netherlands (2010), Assman (1998), Bobbio (1992); Butler (2017), Bourdieu (2003), Candau (2009), Gatti (2010), Hawls (2000), Imbernón (2010) Locke (1983), Tardif (2002), Tavares (2013), Sorj (2004), Shulaman (1986), among others, reflecting data from interviews with two people that make up the discipline management, as well as the results of the questionnaires sent to the teachers who teach the discipline to the courses. bachelor degree. In the analysis the senses of the conception of the discipline thought by the management were revealed. This one that understands the discipline as an education in human rights. The meanings of each term (Diversity, Citizenship and Rights) emerged in an individualized way presented by the teachers that minister the discipline and participated in the questionnaire. In conclusion, it was understood that the discipline is innovative and has met the expectation of human rights education, but the management must intensify the training of teachers who have an interest in teaching the discipline, requiring them as a requirement for remaining to be allocated in the subject.